Prolonged incremental tests do not necessarily compromise VO2max in well-trained athletes - Pierce, S. J.; Hahn, A. G.; Davie, A.; Lawton, E. W. (Journal of Science and Medicine in Sport, 1999)
Existing literature suggests that tests for maximal oxygen uptake (VO2max) should last 8-12 minutes and that prolonged tests do not produce valid measurements. The research underlying this suggestion has been performed with non-athletic populations and trained athletes may be more tolerant of longer protocols. Eleven rowers (8 males, 3 females) each underwent four different incremental tests on a standard rowing ergometer in randomised counterbalanced order. One of the tests was continuous with workload increments each minute (IT1MIN). This test lasted an average of 12 min+/-4 s (SEM). The other three tests were discontinuous and consisted of 7 stages separated by 1-minute recovery intervals. Stage durations of 3, 4 and 5 min were used in the different tests (IT3MIN, IT4MIN and IT5MIN). Mean values for VO2max were almost identical for IT1MIN (4.56+/-0.22 L x min(-1)), IT3MIN (4.60+/-0.23 L x min(-1)) and IT4MIN (4.60+/-0.21 L x min(-1)), while IT5MIN produced a significantly lower value (4.47+/-0.21 L x min(-1), p<0.05). There was no significant difference between protocols in peak post-exercise blood lactate concentration (approx 13 mmol x L(-1) in each case), but IT1MIN produced lower peak heart rates and higher respiratory exchange ratios. We conclude that with well trained rowing athletes discontinuous test protocols involving 7 stages of 3-4 minutes duration can provide valid measurements of VO2max.